Obstruction of justice in the effort to eradicate corruption in Indonesia - Isra, Saldi (International journal of law, crime and justice, 2017)
Corruption is a reality in Indonesia and has a significant destructive force. Not only does it harm the wealth of the state, but it also takes away the legitimacy of law enforcement by destroying the public's trust in law. This can lead to the destruction of democracy and modernization in Indonesia. Aware of the situation, or perhaps for political correctness, the post independence governments made the war on corruption a state of emergency. But it was not until the advent of the political era known to the Indonesians as Era Reformasi in 2000 that the fight against corruption intensified with the enactment of Law No. 30/2002 creating the Corruption Eradication Commission or Komisi Pemberantasan Korupsi (hereafter referred to as KPK). Since its creation, the Commission has been hunting down corruptors like never before. But going after corrupt officials is not an easy task. As KPK gets tougher due to more legal backup and public's trust, corruptors find illegal ways to bend, or impede the law in order to get away with their heinous crime. This practice is known as obstruction of justice. This paper discusses the issue of obstruction of justice in the effort to eradicate corruption in Indonesia. It sets out to answer the following questions: what does obstruction of justice in the corruption eradication effort look like in Indonesia, and how can law enforcement agencies best deal with it. Drawing on empirical data, the study reveals that an act is deemed obstructing justice if it is done intentionally to prevent the legal process from running smoothly (mens rea). Although anyone is susceptible of committing an act of obstruction of justice, it is usually accomplished with the support of affluent people such as government and law enforcement officials, lawyers, and law makers. The study suggests that revising laws on corruption, continuing collaboration between law enforcement agencies, making use of the existing corruption-related laws, increasing law enforcement professionalism, and raising public awareness need to be embraced as future approaches to heighten the ongoing war on corruption.